Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan Terhadap Kemandirian Keuangan Daerah Dengan alokasi Belanja Modal Sebagai Mediasi (Studi Kasus Pemerintah Kota Payakumbuh tahun 2018-2023) - Rini Desanty; Anne Putri (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
This study aims to analyse the effect of Local Revenue (PAD) and Balancing Funds on Regional Financial Independence with Capital Expenditure as a mediating variable in Payakumbuh City. This study is based on the high fiscal dependence of the Payakumbuh City Government on transfer income from the central government, although PAD has shown an increasing trend in recent years. The data shows that the average ratio of regional financial independence is still relatively low, which is 18.26%, while the average financial dependence ratio reaches 80.61%. The method used is quantitative analysis to see the direct and indirect effects between variables using SEM-PLS. The results of the study show that PAD has a significant positive effect on financial independence, while balancing funds have a significant negative effect. Capital expenditure does not mediate the effect of PAD on independence but negatively mediates the effect of balancing funds on independence. These findings indicate that the allocation of capital expenditure has not been effective in increasing fiscal independence and the need to increase the effectiveness of PAD and optimise capital expenditure to reduce fiscal dependence on the central government.